Improving students' critical thinking: Empirical support for explicit instructions combined with practice - Heijltjes, Anita; Van Gog, Tamara; Paas, Fred (John Wiley and Sons Ltd, 2014)
This experiment investigated the impact of different types of critical thinking instruction and dispositions on bias in economics students' (N=141) reasoning performance. The following conditions were compared: (A) implicit instruction; (B) implicit instruction with practice; (C) implicit instruction with explicit instruction and practice; (D) implicit instruction with explicit instruction, practice, and self-explanation prompts; and (E) implicit instruction with explicit instruction, practice, and activation prompts. Results showed that explicit instruction combined with practice is required to improve critical thinking (i.e., conditions A/B<C/D/E). Prompting during practice had no added performance benefits. Participants' dispositions toward actively open-minded thinking predicted their pre-test and post-test scores but did not interact with instruction condition, suggesting that receiving explicit instruction combined with practice was equally effective for all students.
Keywords: Experimental and Cognitive Psychology; Arts and Humanities (miscellaneous); Developmental and Educational Psychology